Smart Defense 5.0 Concept to Protect the Indonesian Capital City (IKN) - Putra, Hendriman; Mulyono, Budi Eko (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This article aims to analyze and evaluate the implementation of the smart defense 5.0 concept in order to secure the Indonesian Capital City (IKN). This research was conducted through an in-depth literature study of various sources, including government documents, scientific publications, and media reports. Qualitative descriptive methods were used to analyze the data obtained. The results of the study indicate that the smart defense 5.0 concept has enormous potential in improving the security of the IKN by integrating information technology and artificial intelligence. However, the implementation of this concept still faces a number of challenges, such as limited technological infrastructure, coordination between institutions and human resource readiness. This study provides policy recommendations to accelerate and improve the effectiveness of the implementation of smart defense 5.0 in the IKN.